Antifungal Properties of Selected Medicinal Plant Species Against Fusarium spp. – A Preliminary Study - Abu Bakar, Izza Nadira; Abdul Razak, Abdul Raffar; Zulkifle, Muhammad Nur Hakim; Rosli, Nur Aliah; Kuok San, Yeo Freddy (Borneo Journal of Resource Science and Technology, 2018)
Usage of synthetic fungicides has inevitably been one of the agricultural practices in combating crop pathogens and maintaining the quality of production. Although fungicides have been proven to be profoundly effective, excessive and frequent reliance on these synthetic fungicides have caused negative impacts to the environment and human health. Besides that, indiscriminate use of fungicides may lead to the development of resistant strains of pathogenic fungi. The need to find an alternative solution to synthetic fungicides has led to the interest in finding plant-based fungicides. This study aimed to test the antifungal properties of plant extracts from 13 different medicinal plant species towards plant pathogenic fungi. Absolute methanol was used as a solvent to extract the secondary metabolites from the different plant species. The effect of methanolic crude extract at different concentrations (500 g/ml, 250 g/ml and 100 g/ml), from different medicinal plant species, were tested on the growth of two Fusarium spp., FsB and FsP. The assay showed that the methanolic crude extract from six plant species viz. Alpinia galanga, Annona muricata, Archidendron jiringa, Nephelium lappaceum, Polygonum minus and Artocarpus hybrid (Nanchem) had successfully inhibit the radial mycelial growth of either FsB or FsP, or both. The assay suggested that the six plant species have antifungal properties towards the crop pathogenic fungi tested. Keywords: antimicrobial, Fusarium, plant extracts, methanolic extracts, biofungicides